Neighbourhood child poverty in Sweden - Björn Gustafsson; Torun Österberg (Institute for the Study of Labor (IZA), 2010)
This paper takes a fresh look at child poverty at the neighbourhood level in the three metropolitan regions of Sweden using unique data for 1990, 1996 and 2002. We find that the number of neighbourhoods with high child poverty rates is much larger in 2002 than in 1990, but also that most poor children in the three regions live outside poor neighbourhoods. A disproportionally large fraction of children with backgrounds from low- and middle-income countries live in poor neighbourhoods. Regression analysis shows that high neighbourhood poverty rates are mainly due to parents' low employment and to low parental education.
Keywords: I32; J13; R23; 330; Child poverty; neighbourhood; Sweden; Kinder; Armut; Nachbarschaftsökonomie; Ballungsraum; Schweden